Dampak Penggunaan Media Sosial Whatsapp terhadap Interaksi Sosial Masyarakat Desa Lok Batu Kabupaten Balangan - diah, Halimatus Sa'; Khairussalam, Khairussalam; Hakim, Arif Rahman (Laboratorium Sosiologi FISIP Universitas Jember, 2022)
This research is motivated by the development of increasingly sophisticated technology. WhatsApp social media is a means for interacting, sharing information, education and entertainment. So that the use of WhatsApp social media has its own impact on its users. This study aims to: (1) To determine the use of WhatsApp on the social interaction of the people of Lok Batu Village, Batu Mandi District, Balangan Regency. (2) Identifying and understanding the positive and negative impacts of using WhatsApp in the Lok Batu village, Batu Mandi District, Balangan Regency. This research method uses a qualitative research approach with a qualitative descriptive type of research. The informants in this study were the people in the village of Lok Batu. Data collection techniques used in this study were observation, interviews and documentation, with primary and secondary data sources. Data analysis technique using triangulation technique. This research was reviewed using Social Interaction theory by Gillin and Gillin. From the results of research that has been carried out, it is found that the use of WhatsApp in Lok Batu village is used as a communication tool that makes it easier for users to interact remotely. Through various available WhatsApp features such as group chats, voice calls, video calls, sharing photos, videos and documents. If WhatsApp is used wisely it will have a positive impact on WhatsApp users, but if it is misused it will have a negative impact on WhatsApp users and society. In this case, the author looks at the impact of using WhatsApp social media in terms of Social Relations, and the functions of the media, namely the Information Function, Educational Function and Entertainment Function. The positive impact of social relations (strengthening friendships, keeping yourself from being less social and as a forum for exchanging ideas) negative impacts (irritability, forgetting time and spending time on WhatsApp). The positive impact of the Information Function (Notification of the latest news that can be easily spread and as a forum to promote business) the negative impact of the information function (easily consumed by hoax news). The positive impact of the Educational Function (increased knowledge and as a medium of online learning). Positive impact Entertainment function (as an entertainment medium) negative impact (triggering social jealousy and excessive joking).Keywords: Impact, WhatsApp, Social Interaction, Lok Batu Village. Penelitian ini dilatar belakangi dengan seiring perkembangan zaman teknologi semakin canggih. Media sosial WhatsApp menjadi sarana untuk berinteraksi, berbagi informasi, edukasi dan hiburan. Sehingga penggunaan media sosial WhatsApp memiliki dampak tersendiri terhadap penggunanya. Penelitian ini bertujuan untuk : (1) Untuk mengetahui penggunaan WhatsApp terhadap interaksi sosial masyarakat Desa Lok Batu Kecamatan Batu Mandi Kabupaten Balangan. (2) Mengidentifikasi juga memahami dampak positif dan negatif penggunaan WhatsApp masyarakat di kampung Lok Batu Kecamatan Batu Mandi Kabupaten Balangan. Metode penelitian ini menggunakan pendekatan penelitian kualitatif dengan tipe penelitian deskriptif kualitatif. Informan dalam penelitian ini adalah Masyarakat di desa Lok Batu. Dari hasil penelitian yang telah dilaksanakan, didapatkan hasil bahwa penggunaan WhatsApp di desa Lok Batu digunakan sebagai alat komunikasi yang memudahkan penggunanya untuk dapat berinteraksi dengan jarak jauh. Melalui berbagai fitur WhatsApp yang tersedia seperti chat grup, panggilan suara, panggilan video, berbagi foto, video dan dokumen. Dari sisi Hubungan Sosial, dan Fungsi media yaitu Fungsi Informasi, Fungsi Edukasi dan Fungsi Entertaimen (Hiburan). Dampak positif hubungan sosial (mempererat silaturahmi, menjaga diri agar tidak kurang pergaulan dan sebagai wadah untuk bertukar pikiran) dampak negatif (mudah tersinggung, lupa waktu dan menghabiskan waktu dengan WhatsApp). Kata Kunci : Dampak, WhatsApp, Interaksi Sosial, Desa Lok Batu